Determinants Of Financial Performance Influencing Fiscal Reserves In Indonesia: The Moderating Role Of Expenditure Harmony: a Study of All Second-Level Local Governments in Indonesia - Handy, Viendy Lugina; Fitrijanti, Tettet; Poulus, Sugiono (Jurnal Manajemen Bisnis, 2026)
This research aims to determine the effect of regional governments finance independency, regional governments financial effectiveness, and SiLPA growth on fiscal reserves in Indonesian Local Governments with Expenditure Harmony as a moderating variable. The population used in this study is all Local Governments in Indonesia with a research period from 2018 to 2022. The results of this study show that regional governments finance independency and regional governments financial effectiveness have a significant direct effect on fiscal reserves in Indonesia, while SiLPA growth does not have an effect on fiscal reserves in Indonesia. Regional governments financial independency and SiLPA growth moderated by expenditure harmony do not have an effect on fiscal reserves in Indonesia, while regional governments financial effectiveness moderated by expenditure harmony has an effect on fiscal reserves in Indonesia.